Benin : Sixth Review Under the Extended Credit Facility Arrangement and Request for a Waiver of Nonobservance of a Performance Criterion. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Benin's Sixth Review Under the Extended Credit Facility (ECF) Arrangement and Request for a Waiver of Nonobservance of a Performance Criterion (PC). The last review of Benin's ECF arrangement confirms the improved growth performance during the program. Real GDP growth is expected to reach about 5 1\2 percent in 2014 for the third consecutive year. The government is tackling emerging issues in several areas to reduce risks to the good macroeconomic performance. The IMF staff recommends completion of the review and supports the authorities' request for a waiver of the PCs on nonconcessional borrowing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet